Protective Effects of Lactic Acid Bacteria Against TLR4 Induced Inflammatory Response in Hepatoma HepG2 Cells Through Modulation of Toll-Like Receptor Negative Regulators of Mitogen-Activated Protein Kinase and NF-κB Signaling - Kanmani, Paulraj; Kim, Hojun (Frontiers in Immunology, 2018)
The beneficial effects of probiotics in several liver diseases have been investigated in both animal and clinical models; however, the precise mechanisms responsible for their effects have not yet been elucidated. Gut transmitted endotoxins such as LPS have been shown to play critical roles in hepatic inflammation and injury. Therefore, in this study, we investigated the beneficial role of selected lactic acid bacteria (LABs) on reduction of hepatic steatosis and attenuation of LPS induced inflammatory response in vitro. Total cellular fluid (TCF) of LABs treatment reduced hepatic steatosis by decreasing the amount of lipid accumulation in vitro. Additionally, HepG2 cells exposed to LPS showed increased expression of exacerbated inflammatory cytokines such as IL-6, CXCL8, CCL2 and TNF-, but these effects were counteracted when cells were treated with TCF of LABs prior to LPS challenge. Moreover, TCF of LABs was able to modulate mRNA levels of TLR negative regulators and protein levels of p38 MAPK and p65 NF-κB transcription factors. However, these modulations were differed remarkably between both FFA treated and untreated HepG2 cells. Heat-killed LABs were also indirectly suppressed THP-1 cells to produce higher level of IL-10, TLR4, and lower at genes level of TGF-β, IL-1β and IL-6, and at protein level of TNF-α in response to LPSvitro. Taken together, our findings indicate that selected LABs exhibit profound immunoregulatory effects on liver cells via modulation of TLR negative regulators of the MAPK and NF-κB pathways.